Climate versus human-driven fire regimes in Mediterranean landscapes: the Holocene record of Lago dell’Accesa (Tuscany, Italy) - Vannière, B; Colombaroli, D; Chapron, E; Leroux, A; Tinner, W; Magny, M (Quaternary Science Reviews, 2008)
A high-resolution sedimentary charcoal record from Lago dell’Accesa in southern Tuscany reveals numerous changes in fire regime over the last 11.6kyr cal.BP and provides one of the longest gap-free series from Italy and the Mediterranean region. Charcoal analyses are coupled with gamma density measurements, organic-content analyses, and pollen counts to provide data about sedimentation and vegetation history. A comparison between fire frequency and lake-level reconstructions from the same site is used to address the centennial variability of fire regimes and its linkage to hydrological processes. Our data reveal strong relationships among climate, fire, vegetation, and land-use and attest to the paramount importance of fire in Mediterranean ecosystems. The mean fire interval (MFI) for the entire Holocene was estimated to be 150yr, with a minimum around 80yr and a maximum around 450yr. Between 11.6 and 3.6kyrcal.BP, up to eight high-frequency fire phases lasting 300–500yr generally occurred during shifts towards low lake-level stands (ca 11,300, 10,700, 9500, 8700, 7600, 6200, 5300, 3400, 1800 and 1350cal. yrBP). Therefore, we assume that most of these shifts were triggered by drier climatic conditions and especially a dry summer season that promoted ignition and biomass burning. At the beginning of the Holocene, high climate seasonality favoured fire expansion in this region, as inmany other ecosystems of the northern and southern hemispheres. Human impact affected fire regimes and especially fire frequencies since the Neolithic (ca 8000–4000cal.yrBP). Burning as a consequence of anthropogenic activities becamemore frequent after the onset of the Bronze Age (ca 3800–3600cal. yrBP) and appear to be synchronous with the development of settlements in the region, slash-and-burn agriculture, animal husbandry, and mineral exploitation. The anthropogenic phases with maximum fire activity corresponded to greater sensitivity of the vegetation and triggered significant changes in vegetational communities (e.g. temporal declines of Quercus ilex forests and expansion of shrublands and macchia). The link between fire and climate persisted during the mid- and late Holocene, when human impact on vegetation and the fire regime was high. This finding suggests that climatic conditions were important for fire occurrence even under strongly humanised ecosystem conditions.
Keywords: CHARCOAL ANALYSIS; Climatic conditions; Fire regime; Holocene; human activities; Pollen analysis; Vegetation history (voyant)

Climate versus human-driven fire regimes in Mediterranean landscapes: the Holocene record of Lago dell’Accesa (Tuscany, Italy) - Vannière, B.; Colombaroli, D.; Chapron, E.; Leroux, A.; Tinner, W.; Magny, M. (Quaternary Science Reviews, 2008)
A high-resolution sedimentary charcoal record from Lago dell’Accesa in southern Tuscany reveals numerous changes in fire regime over the last 11.6kyr cal.BP and provides one of the longest gap-free series from Italy and the Mediterranean region. Charcoal analyses are coupled with gamma density measurements, organic-content analyses, and pollen counts to provide data about sedimentation and vegetation history. A comparison between fire frequency and lake-level reconstructions from the same site is used to address the centennial variability of fire regimes and its linkage to hydrological processes. Our data reveal strong relationships among climate, fire, vegetation, and land-use and attest to the paramount importance of fire in Mediterranean ecosystems. The mean fire interval (MFI) for the entire Holocene was estimated to be 150yr, with a minimum around 80yr and a maximum around 450yr. Between 11.6 and 3.6kyrcal.BP, up to eight high-frequency fire phases lasting 300–500yr generally occurred during shifts towards low lake-level stands (ca 11,300, 10,700, 9500, 8700, 7600, 6200, 5300, 3400, 1800 and 1350cal. yrBP). Therefore, we assume that most of these shifts were triggered by drier climatic conditions and especially a dry summer season that promoted ignition and biomass burning. At the beginning of the Holocene, high climate seasonality favoured fire expansion in this region, as inmany other ecosystems of the northern and southern hemispheres. Human impact affected fire regimes and especially fire frequencies since the Neolithic (ca 8000–4000cal.yrBP). Burning as a consequence of anthropogenic activities becamemore frequent after the onset of the Bronze Age (ca 3800–3600cal. yrBP) and appear to be synchronous with the development of settlements in the region, slash-and-burn agriculture, animal husbandry, and mineral exploitation. The anthropogenic phases with maximum fire activity corresponded to greater sensitivity of the vegetation and triggered significant changes in vegetational communities (e.g. temporal declines of Quercus ilex forests and expansion of shrublands and macchia). The link between fire and climate persisted during the mid- and late Holocene, when human impact on vegetation and the fire regime was high. This finding suggests that climatic conditions were important for fire occurrence even under strongly humanised ecosystem conditions.
Keywords: CHARCOAL ANALYSIS; Climatic conditions; Fire regime; Holocene; human activities; Pollen analysis; Vegetation history (voyant)

Structure, biomass and production of a resprouted holm-oak (Quercus ilex L.) forest in NE Spain - LLEDO, M J; Sánchez, J R; Bellot, J; Boronat, J (Plant Ecology, 1992)
When considered as a compartment of nutrients (biomass) and as a flux between compartments (pro- duction) vegetation plays an important role in the biogeochemical forest research that is carried out at the Prades research station in two adjacent catchments: L'Avic (51.6 ha) and La Teula (38.5 ha). The forest density at the Prades site, considering both the tree and shrub layers, is 9182 stems ha t, with 4527 stems ha i being the tree layer. The predominant species is Quercus ilex with Arbutus unedo and Phillyrea media less common. The structure of the population, estimated by grouping the numbers of the stems in classes of 2.5 cm, shows a distribution which conforms, in both catchments, to a negative exponential equation following the Yoda law. The distribution observed at different altitudes shows great heterogeneity, the number of stems of Q. ilex increases with altitude, from 4000 stems ha ~ at 800 m, to 14000 stems ha 1 at 1000 m of altitude. The upper and the lower parts of the watershed show dif- ferences in forest production that explain this variation. In this paper the influence of human activities and physical factors on the origin of this structure is discussed. The tree and shrub biomass was cal- culated by applying allometric regressions for the three predominant species and has been estimated as 113.2 t ha 1. The tree layer accounts for 92°o. Net production was calculated from annual increases (by differences between the 1981 and 1986 basal area measures) of the woody part and the litterfall. The above-ground net production was about 6.5 t ha 1 year 1, 95.4o0 of it being from trees and shrubs and only 4.6°0 from grasses.
Keywords: Forest structure; human activities; mediterranean forest; prades; Species distribution

Changes and disturbances of forest ecosystems caused by human activities in the western part of the Mediterranean basin - Barbero, M; Bonin, G; Loisel, R; Quezel, P (Plant Ecology, 1990)
The development of socio-economic activity over the past ten years in the Mediterranean region has induced severe changes in the main natural forest ecosystems. In the northern Mediterranean, rural depopulation has accelerated since the end of the second World War, particularly since the establishment of Common Market agricultural policies, and led to an under-utilization of species causing a strong biological resurgence of the forest, even at high altitudes. This means that, at the present time, the extension of expansion model coniferous forests is favored by their capacities for spatial, biological and ecological selection. Along with this, the under-utilization of sclero- phyllous (resistance model) and deciduous (stabilization model) oak coppices has led to the establishment of new forest structures and architectures which are notably different from the main climatic groups defined up to now by phytosociological and synchronic methods. Two new forms of disturbances have appeared: - increasingly important wild fires have replaced disturbances caused by burn beating and are at the origin of the very strong spatial and temporal heterogeneity of current forest species. - In addition, the geographical continuity of the main groups of same-aged sclerophyllous and deciduous species, due to their non-use over the past ten years, has accelerated a phytosanitary imbalance by an increase in the action of pests. In the southern Mediterranean, particularly in North Africa, demographic pressure and grazing have widely disturbed the main forest ecosystems which show a continual regression of their surface. Many forest tree species with a low spatial and biological selection, such as Mediterranean firs and black pines (Pinus nigra subsp, mauritanica), are threatened with extinction, as are the deciduous oak forests which, considering the climatic stress and edaphic constraints, are permanently in a state of imbalance. Human disturbances induce a complete modification of structures and architectures tending towards the instal- lation of simplified forest models (trees-grasses) where tree regeneration is nearly impossible. The sclero- phyllous coppices well-adapted to stress are also threatened by shorter and shorter cutting cycles and by the high usage of tree canopies for grazing. - The forest understory structures have witnessed a decrease in their characteristic sylvatic species and the matorralization of most of the forests can be seen by the replacement of typical forest groups by preforest groups (Tetraclinis forests, Aleppo pine forests). - New geopedological constraints linked to the removal of the surface soil layer combined with regular climatic stress (duration of drought periods) strongly decrease the resilience of these ecosystems which are under continual pressure (unbalanced models). - In diverse regions, particulary in semi-arid bioclimates, hyperdegradation affects the shrub cover which disappears for a time in favor of perennial grasses (forest steppization): Andropogon div. sp., Ampelodesmos, Stipa div. sp. In all bioclimatic groups, the increase in grazing pressure throughout the southern Mediterranean ecosystems can even lead to the total disappearance of perennial species from the ecosystem with the exception of the dominant tree. Regardless of the altitude or ecosystem, invasive therophytes are then the only plants to occupy the understory and indicate hyperdegradation (forest therophytization).
Keywords: changes; disturbances; dynamic models; human activities; Mediterranean forests